2013
DOI: 10.1136/emermed-2012-202168
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic response to morphine in obese and morbidly obese patients in the emergency department

Abstract: Obesity status did not influence analgesic response to a fixed dose of morphine. This suggests that obese and morbidly obese patients do not require a higher dose of morphine for acute pain reduction compared to non-obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…However, in studies suggesting a size descriptor for dosing opioids, recommendations were for IBW, lean body mass, or adjusted body weight as a preferred descriptor. While no prospective studies are available that compare weight-based dosing of opioids in obese and normal weight critically ill patients, prospective and retrospective studies performed in the emergency department and postoperative setting have consistently found large variations in opioid requirements and pain control in overweight and obese patients that had no relationship to ABW [13][14][15][16]. Similarly, pharmacokinetic studies evaluating various opioids in the perioperative setting have found opioid doses based on ABW are likely to be excessive as evidenced by pharmacokinetic parameters and measured opioid concentrations [17][18][19][20][21][22].…”
Section: Analgesia Opioidsmentioning
confidence: 99%
“…However, in studies suggesting a size descriptor for dosing opioids, recommendations were for IBW, lean body mass, or adjusted body weight as a preferred descriptor. While no prospective studies are available that compare weight-based dosing of opioids in obese and normal weight critically ill patients, prospective and retrospective studies performed in the emergency department and postoperative setting have consistently found large variations in opioid requirements and pain control in overweight and obese patients that had no relationship to ABW [13][14][15][16]. Similarly, pharmacokinetic studies evaluating various opioids in the perioperative setting have found opioid doses based on ABW are likely to be excessive as evidenced by pharmacokinetic parameters and measured opioid concentrations [17][18][19][20][21][22].…”
Section: Analgesia Opioidsmentioning
confidence: 99%
“…However, BMI did not influence the positive analgesic response to a 4-mg fixed dose of morphine administered to morbidly obese, obese, overweight, and normal-weight individuals in the emergency department setting. 182 Similarly, frovatriptan, in contrast to other triptans, retained a sustained antimigraine effect on obese subjects, possibly because of its longer half-life. 183 Chronic pain pharmacotherapy should address the concerns of obese patients about iatrogenic weight gain associated with some commonly used pain medications, such as gabapentin or pregabalin.…”
Section: Pharmacotherapy For Pain In Obese Patientsmentioning
confidence: 99%
“…It has been argued that clearance of fentanyl is affected by obesity, is significantly higher in obese patients and that fentanyl dosing should be based on LBW, as administration according to total body weight may lead to an overdose in the obese (30). On the other hand, oral morphine seems not to be affected by obesity (46). As fentanyl is lipophilic, obesity should affect its pharmacokinetic profiles, while a high amount of adipose tissue could result in a prolonged beta half life.…”
Section: Discussionmentioning
confidence: 99%